Periodontal Ligament Cells Are Involved in the Formation of Intracanal Cementum-Like Tissue After Regenerative Endodontic Procedures: A Mouse in situ Model - Tomoaki Komada; Keisuke Mitomo; Takatoshi Ikarashi; Masaki Shimono; Han-Sung Jung; Takashi Muramatsu (Frontiers Media S.A., 2022)
Regenerative endodontic cell-homing procedures are frequently performed on injured immature teeth diagnosed with pulp necrosis and/or apical periodontitis. The representative histological finding after those procedures is cementum-like tissues filling in the root canal but details of the healing process remain unknown. We investigated that healing process histologically using a mouse in situ model. Regenerative endodontic procedures were experimentally performed on noninfected maxillary first molars of 6-week-old male C57BL/6 mice, after which the healing process was investigated using histology and immunohistochemistry. Immediately after the regenerative endodontic cell-homing procedures, blood clots were seen in the root canals that disappeared over time. On day 7, the blot clot in the root canal was replaced by granulation tissue. From day 14 onward, cementum-like tissues were filled in the root canals, while the amount of fibrous tissue was reduced. Immunohistochemically, positive reactions for periostin were seen in the fibrous tissue in the root canal, the apex, and periodontal ligament cells. On the other hand, positive reactions for nestin were not detected in the root canal. CD31-positive cells with a luminal structure were also observed in the fibrous tissue around the apex and around the newly formed cementum-like tissues in the root canal. Thus, in this study, we have established an in situ mouse model of regenerative endodontic procedures. The results of this study suggest that periodontal ligament cells and vascular endothelial cells grow into the root canals from the apex, replace the blood clots, and participate in the formation of cementum-like tissues with angiogenesis during the healing process of regenerative endodontic procedures.